Biomimetic crosslinking of collagen gels by energetic electrons: The role of L-lysine. (1st March 2022) - Wilharm, Nils; Bertmer, Marko; Knolle, Wolfgang; Griebel, Jan; Elsner, Christian; Mayr, Stefan G.
Abstract: Energetic electrons have recently evolved as a powerful tool for crosslinking bio-derived hydrogels without the need for adding potentially hazardous reagents. Application of this approach allows for synthesis of biomimetic collagen-derived networks of highly tunable properties and functionalization. Yet, the underlying reaction kinetics are still not sufficiently established at this point. While hydroxyl radicals are generated by energetic electron-induced hydrolysis of water and play a key role in introducing covalent bonds between network fibers, a detailed mechanistic understanding would significantly increase applicability. We present a comprehensive analysis of central aspects of the reactivity between the hydroxyl radical ( OH) and collagen, elastin, glycine (Gly) and l -lysine (Lys). Pulse radiolysis (PR), solid state nuclear magnetic resonance (NMR), ultraviolet-visible absorption spectroscopy (UV/VIS) and electron spray ionization mass spectrometry (ESI-MS) shine light on distinct features of the crosslinking process. These highlight retained protein backbone integrity in collagen and elastin whilst Lys's ability to form several imine bonded Lys-Lys-species suggests striking similarities to crosslinking via lysyl oxidase catalysis in vivo. Thus, energetic electron based crosslinking opens the venue for customized hybrid gels of outstanding biomimicry and –compatibility. Statement of significance: Energetic electron beam treatment constitutes a highly attractive approach to establish chemical bonds between (bio) molecules. Although a convincing number of publications showed the versatility regarding crosslinking of bioderived hydrogels, insights into the underlying chemistry are still unestablished at this point. The present work unravels the mechanistics of energetic electron induced processes in collagen and elastin hydrogels as well as several abundant amino acids in aqueous solution. As key finding we demonstrate, that i) the connection between polymer chains is dominated by amino acid side chain interaction and ii) two single l -lysine molecules form an imine bond between the terminal amino group of one molecule and the delta carbon of the second molecule. We also consider the formation of H-bonds as a second crosslinking pathway. These findings open up for advanced, optionally spatially resolved biomaterials design. Graphical abstract: Image, graphical abstract